Heterochromatin is a quantitative trait associated with spontaneous epiallele formation - Yinwen Zhang (Nature Portfolio, 2021)
The molecular origins of epialleles remain unknown. Here, the authors show that a positive feedback loop between H3K9me2 and CMT2/3 is a major contributing factor to the origins of spontaneous epialleles and that heterochromatin is a quantitative trait associated with spontaneous epiallele formation.